Covid-19 Anti-lockdown Rallies: A View from America - William D. Slicker (The Thinker)
Much of the world has been under lockdown orders in the past few months, due to fears about the possible impact of Covid-19. As this is a highly contagious virus, there were initial fears that the death rate from Covid-19 would be quite high.